2023
DOI: 10.3390/pharmaceutics15020414
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Evaluation of a Lead Specific Chelator (PSC) Conjugated to Radiopeptides for 203Pb and 212Pb-Based Theranostics

Abstract: 203Pb and 212Pb have emerged as promising theranostic isotopes for image-guided α-particle radionuclide therapy for cancers. Here, we report a cyclen-based Pb specific chelator (PSC) that is conjugated to tyr3-octreotide via a PEG2 linker (PSC-PEG-T) targeting somatostatin receptor subtype 2 (SSTR2). PSC-PEG-T could be labeled efficiently to purified 212Pb at 25 °C and also to 212Bi at 80 °C. Efficient radiolabeling of mixed 212Pb and 212Bi in PSC-PEG-T was also observed at 80 °C. Post radiolabeling, stable Pb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

5
3

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…[ 203 Pb]Pb-MC1L surrogate was injected in the same animal model to determine the in vivo biodistribution for calculating the dosimetry of [ 203 Pb]Pb-MC1L in normal organs. Our prior studies have demonstrated excellent chelation kinetics and stability with PSC for [ 212 Pb] and [ 212 Bi][8]. However previous literature has shown that during a fraction of [ 212 Pb] disintegrations, the daughter [ 212 Bi] cations are released from the chelator[25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 203 Pb]Pb-MC1L surrogate was injected in the same animal model to determine the in vivo biodistribution for calculating the dosimetry of [ 203 Pb]Pb-MC1L in normal organs. Our prior studies have demonstrated excellent chelation kinetics and stability with PSC for [ 212 Pb] and [ 212 Bi][8]. However previous literature has shown that during a fraction of [ 212 Pb] disintegrations, the daughter [ 212 Bi] cations are released from the chelator[25].…”
Section: Discussionmentioning
confidence: 99%
“…Among commercially available α-emitters, [ 212 Pb] (half-life T 1/2 10.6 h) is produced using a [ 224 Ra]/[ 212 Pb] generator system that enables nimble on-demand production of [ 212 Pb]Pb-based radiopharmaceuticals[7]. In the case of [ 212 Pb], the isotope [ 203 Pb] (T 1/2 51.9 h) can be used as a single-photon emission computerized tomography (SPECT) imaging diagnostic companion to provide detailed dosimetry that guides [ 212 Pb] therapy dosing [8]. The [ 203 Pb]/[ 212 Pb] radionuclide pair has the advantage that elementally identical imaging surrogate [ 203 Pb] can guide [ 212 Pb] therapy ( Figure 1b ).…”
Section: Introductionmentioning
confidence: 99%
“…This may be less so with the use of relatively short-lived 212 Pb because the recoil energy of the β-particle emission of 212 Pb is significantly less than the binding energy of the daughter nucleus to the chelator. Although reports of Bi instability to decoupling has been reported for DOTA and TCMC [ 44 , 45 ], recent reports of a new chelator with improved stability of the chelator 212 Bi coupling represents an advance that can improve the therapeutic index for targeting ligands conjugated to this new chelator (known as Pb-Specific-Chelator or PSC) [ 46 , 47 , 48 , 49 ].…”
Section: Targeted Alpha Therapy (Tat)mentioning
confidence: 99%
“…[2][3][4][5] VMT-α-peptide, a novel molecule which targets the somatostatin receptor subtype-2 (SSTR2), has demonstrated promising results in preclinical studies for targeted α therapy in Neuroendocrine Tumors (NETs). 6…”
mentioning
confidence: 99%
“…Ongoing research, both preclinical and clinical, is actively investigating the use of peptides and antibodies labeled with 212 Pb 2–5 . VMT-α-peptide, a novel molecule which targets the somatostatin receptor subtype-2 (SSTR2), has demonstrated promising results in preclinical studies for targeted α therapy in Neuroendocrine Tumors (NETs) 6 . SPECT/CT imaging with 212 Pb VMT-α-NET has shown immediate tumor accumulation, high tumor retention, and rapid renal excretion, indicating its potential effectiveness as seen in our case.…”
mentioning
confidence: 99%